The ICT-Based PBT Model in Poetry Learning in Madrasah in the Era of Industrial Revolution 4.0 - Faridhatun Nikmah; Haryadi; Nas Haryati Setyaningsih; Elen Inderasari (Widyantara, 2023)
The problems that occur today show that most teachers in doing learning are more teacher-center-based where the learning is teacher-centered. This is what causes learning to tend to be monotonous so that learning becomes less active. To anticipate these problems, it is necessary to have a variety of learning models so that learning can be active, creative, innovative, and fun. The purpose of this study is to determine the application of poetry learning using the PBT model in facing the era of revolution 4.0 and to determine the application of ICT-based PBT learning in facing the era of the industrial revolution 4.0. The method used in this study is descriptive qualitative by describing the data in depth which is then relevant to the theory relevant to the research. The results of this study show that the application of poetry learning with the PBT model is carried out by 1) providing introduction and motivation, 2) providing direction for project assignments, 3) monitoring project progress, 4) making videos, 5) assessing work results, and 6) evaluating the learning process. Theapplication of ICT-based PBT learning models is very relevant to the era of the industrial revolution 4.0 where this era requires teachers to utilize technology in learning so that this learning is used as a form of breakthrough in improving learning in madrasah in the era of the industrial revolution 4.0.